Predictive Factor of Large‐Volume Central Lymph Node Metastasis in Clinical N0 Papillary Thyroid Carcinoma Patients Underwent Total Thyroidectomy - Huang, Jianhao; Song, Muye; Shi, Hongyan; Huang, Ziyang; Wang, Shujie; Yin, Ying; Huang, Yijie; Du, Jialin; Wang, Sanming; Liu, Yongchen; Wu, Zeyu (Frontiers in Oncology, 2021)
Background Large‐volume central lymph node metastasis (large-volume CLNM) is associated with high recurrence rate in papillary thyroid carcinoma (PTC) patients. However, sensitivity in investigating large-volume CLNM on preoperative ultrasonography (US) is not high. The aim of this study is to investigate the clinical factors associated with large-volume CLNM in clinical N0 PTC patients Methods We reviewed 976 PTC patients undergoing total thyroidectomy with central lymph node dissection during 2017 to 2019. Multivariate logistic regression analysis was performed to identify clinicopathologic risk factors for large-volume CLNM in PTC. Results The rate of large-volume LNM was 4.1% (40 of 967 patients). Multivariate analysis showed that male gender and young age (age<45 years old) were independent risk factors for large-volume CLNM with odds ratios ([OR], 95% confidence interval [CI]) of 2.034 (1.015-4.073) and 2.997 (1.306–6.876), respectively. In papillary thyroid microcarcinoma (PTMC), capsule invasion was associated with large-volume CLNM with OR (95% CI) of 2.845 (1.110–7.288). In conventional papillary thyroid cancer (CPTC), tumor diameter (>2cm) was associated with large-volume CLNM, with OR (95% CI) 3.757 (1.061–13.310), by multivariate analysis. In ROC curve analysis on the diameter of the CPTC tumor, the Area Under Curve (AUC) =0.682(p=0.013), the best cut-off point was selected as 2.0cm. Conclusions Male gender and young age were predictors for large-volume CLNM of cN0 PTC. In addition, cN0 PTMC patient with capsule invasion and cN0 CPTC patient with tumor diameter >2cm were correlated with large-volume CLNM. Total thyroidectomy with central lymph node dissection may be a favorable primary treatment option for those patients rather than active surveillance.